2018
DOI: 10.1016/j.talanta.2017.12.084
|View full text |Cite
|
Sign up to set email alerts
|

Detection and scavenging of hydroxyl radical via D-phenylalanine hydroxylation in human fluids

Abstract: Hydroxyl radical (.OH) is highly reactive, and therefore very short-lived. Finding new means to accurately detect .OH, and testing the ability of known .OH scavengers to neutralize them in human biological fluids would leverage our ability to more effectively counter oxidative (.OH) stress-mediated damage in human diseases. To achieve this, we pursued the evaluation of secondary products resulting from .OH attack, using a detection system based on Fenton reaction-mediated D-phenylalanine (D-Phe) hydroxylation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…(31) Although contradictory results have been reported on the effect of HD on • OH scavenging activity, previous studies using ESR have shown an increase in the scavenging activity, regardless of the generation method of the hydroxyl radicals. (32)(33)(34)(35)(36) Thus, we strongly suggest that the • OH scavenging activity may be restored by HD.…”
Section: Discussionmentioning
confidence: 75%
“…(31) Although contradictory results have been reported on the effect of HD on • OH scavenging activity, previous studies using ESR have shown an increase in the scavenging activity, regardless of the generation method of the hydroxyl radicals. (32)(33)(34)(35)(36) Thus, we strongly suggest that the • OH scavenging activity may be restored by HD.…”
Section: Discussionmentioning
confidence: 75%
“…The antioxidant activity of EXEs was evaluated by the 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid (ABTS), hydroxyl radical (OH), 2-phenyl-4,4,5,5-tetramethylimidazoline-1-oxyl 3-oxide radical (PTIO), and ferric reducing antioxidant power (FRAP) methods, which were improved according to Li (2017) , Biondi et al (2018) , and Gulcin (2020) . The EXE samples with high antioxidant data were selected, gradient diluted, and analyzed for IC 50 values (the concentration at which 50% scavenging of DPPH, ABTS, hydroxyl, PTIO, and ferric was achieved) to evaluate the antioxidant activity of EXEs.…”
Section: Methodsmentioning
confidence: 99%
“…A change in the balance between oxidizing and antioxidant substances in favor of excess oxidants leads to oxidative stress. These systems include enzymes (superoxide dismutase, catalase, and glutathione peroxidase), antioxidant macromolecules (albumin, ceruloplasmin, and ferritin), antioxidant micro-molecules (ascorbic acid, α-tocopherol, β-carotene, ubiquinone, flavonoids and glutathione, methionine, uric acid) bilirubin ( 1 , 158 161 ).…”
Section: Oxidative Stress In Pcos and Cvdmentioning
confidence: 99%
“…ROS are highly reactive molecules with a very short lifespan, and are classified into two categories, namely non-radical species, including hydrogen peroxide (H2O2), hypochlorous acid (HOCl-), ozone (O3-), lipid peroxides (LOOH), along with hydroperoxides (ROOH), and radical species, consisting of superoxide anion (O2•−), singlet oxygen (1O2), hydroperoxyl radical (HOO•), hydroxyl radical (•OH), with •OH being considered the most important ROS ( 158 ). RNS on the other hand comprise a range of various chemical compounds derived from nitric oxide (NO) in the reaction of biologically generated free radicals that tend to form more stable species, a process that generates multiple biological effects ( 162 ).…”
Section: Oxidative Stress In Pcos and Cvdmentioning
confidence: 99%